2021
DOI: 10.3390/su13084124
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Access Control Design for Security Context Awareness in Smart Grid

Abstract: Recently, damages such as internal system intrusion, network and device vulnerability attacks, malicious code infection, and information leakage due to security attacks are increasing within the smart grid environment. Detailed and dynamic access control must be implemented to enable the power system in the smart grid environment to respond to such attacks. Dynamic and partial delegation must be available, and permission role restrictions must be considered for dynamic access control when delegating a role bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The issue of an effective approach to risk management in heterogeneous networks where the technical and data interconnection of the world of ICT and ICS and IoT occurs is a widely discussed and researched topic at present, and the subject of several scientific research topics, as can be concluded from the selected current outputs given below: As mentioned above, smart metering and the whole complex AMM system are considered an integral part of the smart grid, and its security requirements and compliance need to be addressed from this perspective. This security and process perspective is currently the subject of a wide range of research projects and projects: [37].…”
Section: Related Workmentioning
confidence: 99%
“…The issue of an effective approach to risk management in heterogeneous networks where the technical and data interconnection of the world of ICT and ICS and IoT occurs is a widely discussed and researched topic at present, and the subject of several scientific research topics, as can be concluded from the selected current outputs given below: As mentioned above, smart metering and the whole complex AMM system are considered an integral part of the smart grid, and its security requirements and compliance need to be addressed from this perspective. This security and process perspective is currently the subject of a wide range of research projects and projects: [37].…”
Section: Related Workmentioning
confidence: 99%
“…The DFOGI control technique provides power factor correction and harmonic mitigation. Methods for power systems in smart grid environments to cope with security attacks are investigated in the literature [14]. Power systems in smart grid environments can cope with such attacks by implementing detailed and dynamic access control.…”
Section: Introductionmentioning
confidence: 99%